Long-term prognostic impact of pulmonary vascular resistance in patients with rheumatic mitral stenosis undergoing percutaneous mitral balloon valvuloplasty. (3rd October 2022) - Cian Nazzetta, D; De Sousa, L C G; Rosa, V E E; Tessari, F C; Pessoa, R S; Lipari, L F V P; Fernandes, J R C; Lopes, M P; De Santis, A S A L; Spina, G S; Pires, L J N T; Sampaio, R O; et al.
Abstract: Background: Pulmonary hypertension (PH) has a well-known impact on the prognosis of patients with rheumatic mitral stenosis (MS). Some patients can present pre-capillary PH, defined as a pulmonary vascular resistance (PVR) ≥3.0 woods, and there is few data regarding the prognostic value of invasive measures of PVR in this context. Purpose: To assess the impact of PVR on the long-term outcomes of patients with rheumatic MS undergoing percutaneous mitral balloon valvuloplasty (PMBV). Methods: Unicentric, retrospective study, including patients with rheumatic MS undergoing PMBV from 2016 to 2020. All patients underwent clinical and laboratorial evaluation, and transthoracic echocardiogram before and after the procedure. During PMBV, transesophageal echocardiogram and hemodynamic measures were performed. The composite endpoint included death, reintervention and persistent NYHA FC III–IV in long-term follow-up. Results: 58 patients were included with a median age of 50.5 [42–60.5] years and 82.8% were female. Most important comorbidities were hypertension (55.2%), previous valvular intervention (22.4%), diabetes (20.7%), atrial fibrillation (18%), previous stroke/transient ischemic attack (3.4%), coronary artery disease (1.7%). Median mitral valve area was 1.2 [0.9–1.3] cm 2, mean transmitral gradient was 8 [6–12] mmHg and pulmonary artery systolic pressure (PASP) was 42 [35–51] mmHg. Pre-procedure hemodynamic right atrium pressure (RAP) was 8 [6–10] mmHg, pulmonary artery mean pressure (mPAP) was 26 [21–31] mmHg, pulmonary capillary pressure (PCP) was 18 [15–22] mmHg and PVR was 2.15 [1.5–3.46] mmHg/min. Thirty-five (60.3%) patients underwent 1 balloon dilation, 10 (17.2%) 2 dilations, 3 (5.3%) 3 dilations and 1 (1.7%) 4 dilations. Only 1 (1.7%) case need conversion to open surgery. Post-procedure hemodynamic Δ mPAP was 4 [1–8] mmHg, Δ PCP was 5 [2–7] mmHg and Δ PVR was 0.03 [−0.072–0.99] mmHg/min. Median follow-up was 32.9 [20.2–43] months. Need for reintervention (surgery or PMBV) was 6.9%, mortality during follow-up was 1.7% and the composite endpoint occurred in 13 (22.4%) patients. By univariate analysis, echocardiographic PSAP (HR: 1.069, 95% CI 1.010–1.130, p=0.021), RAP (HR: 1.267, 95% CI 1.028–1.562, p=0.027), Δ hemodynamic PASP (HR: 0.927, 95% CI 0.866–0.991, p=0.026) and moderate or severe tricuspid regurgitation (HR: 6.318, 95% CI 1.734–23.023, p=0.005) were associated with the composite endpoint. By multivariate analysis adjusted by RVP, RAP (HR: 1.626, 95% CI 1.005–2.630, p=0.047) was the only independent predictor of the composite endpoint. The RAP cutoff found through the Youden index was 9.5 mmhg (Figure 1). Conclusion: In patients with severe MS undergoing PMBV, RAP measurement in cardiac catheterization was the only independent predictor of combined outcome of death, reintervention and persistent NYHA FC III–IV in long-term follow-up. PVR had no impact on long-term outcomes. Funding Acknowledgement: Type of funding sources: None.